2019
DOI: 10.1155/2019/5647219
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Role of Paeoniflorin in Fluctuant Hyperglycemia-Induced Vascular Endothelial Injuries through Antioxidative and Anti-Inflammatory Effects and Reduction of PKCβ1

Abstract: Hyperglycemia fluctuation is associated with diabetes mellitus (DM) complications when compared to persistent hyperglycemia. Previous studies have shown that paeoniflorin (PF), through its antiapoptosis, anti-inflammation, and antithrombotic properties, effectively protects against cardiovascular and cerebrovascular disease. However, the mechanism underlying the protection from PF against vascular injuries induced by hyperglycemia fluctuations remains poorly understood. Herein, we investigated the potential pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Importantly, a recent study reported that paeoniflorin treatment led to reduced blood glucose levels, inhibited inflammatory factors section, and attenuated glomerular hypertrophy in diabetic rats (32). Similar to this finding, another study showed that paeoniflorin exerts a protective effect on vascular endothelial cells from hyperglycemia fluctuation-induced injury through reducing inflammatory reaction and oxidative stress (33). Our results demonstrated that oral administration of paeoniflorin at 15 or 30 mg/ kg after mating and during the gestation significantly decreased the blood glucose and plasma leptin levels, and increased the insulin levels in rats with GDM.…”
Section: Discussionmentioning
confidence: 56%
“…Importantly, a recent study reported that paeoniflorin treatment led to reduced blood glucose levels, inhibited inflammatory factors section, and attenuated glomerular hypertrophy in diabetic rats (32). Similar to this finding, another study showed that paeoniflorin exerts a protective effect on vascular endothelial cells from hyperglycemia fluctuation-induced injury through reducing inflammatory reaction and oxidative stress (33). Our results demonstrated that oral administration of paeoniflorin at 15 or 30 mg/ kg after mating and during the gestation significantly decreased the blood glucose and plasma leptin levels, and increased the insulin levels in rats with GDM.…”
Section: Discussionmentioning
confidence: 56%
“…21 In addition, the apoptotic endothelial cells can enhance platelet adhesion, promote cell inflammation and lipid infiltration and induce VSMC proliferation, migration, and thrombosis. 22 A previous study has shown that Cur could inhibit intimal hyperplasia and VSMC proliferation following vascular injury. 23 Moreover, it could induce VSMC apoptosis by regulating inflammatory-associated signaling pathways.…”
Section: Discussionmentioning
confidence: 98%
“…23 PF have also been reported to attenuate fluctuant hyperglycemia-induced vascular endothelial injuries, and to improve bleomycin-induced pulmonary fibrosis in rats by suppressing collagen synthesis. 8,24 Besides, the anti-remodeling effect of PF on cardiovascular diseases, including acute myocardial infarction and pressure overload-induced cardiac remodeling, might also contribute to the beneficial effect of PF on PH. 21,25 In the present study, we also found a marked attenuation of the collagen deposition in the pulmonary arterial and RV heart tissue in the PF-treated SuHx rats compared to vehicle-treated SuHx rats.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Paeoniflorin (PF), a monoterpene glucoside extracted from the root of Paeonia lactiflora, possesses many pharmacological activities, such as anti-inflammatory, antioxidative, analgesic, anticancer and immunoregulatory effects. [7][8][9][10] PF is widely used in clinical practice for the treatment of rheumatoid arthritis and systemic lupus erythematosus. 11 A recent study demonstrated that PF exerts a direct vasculoprotective effect through antioxidative and anti-inflammatory effects in fluctuant hyperglycemia-induced vascular endothelial injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation